THE INFLUENCE OF VIDEO LEARNING MEDIA ADDITION ON NEUROMOTORIC PHYSICAL EXAMINATION CLINICAL SKILL OF MEDICAL STUDENT FACULTY OF MEDICINE AND HEALTH SCIENCES JAMBI UNIVERSITY (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2018)
Background: Learning Clinical skills are one of the forms in learning on medical education curriculum which is aimed at improving ability of clinical skills and communication of medical students. Clinical Skill lab (CSL) is a tool for students to learn basic clinical skills whose training will not be detrimental and safe for patient. The addition of video learning media in clinical skills learning is one way to improve medical students clinical skills ability. Research Objectives: This study aims to see the effect of video learning media addition on neuromotoric Physical examination clinical skills of Medical students FKIK UNJA. Method: Experimental research with two groups post-test design only was held at PSKed FKIK UNJA in March-October 2017 and involving 128 students who underwent blok 1.2. The sample was divided into 2 groups and will get two different treatments. The first group had treatment in the form of CSL with was accompaniment by instructor and given the module. In the second group got the same treatment with the addition of a learning media in the form of a neuromotoric examination video. Influence of the treatment was assessed through a final evaluation of clinical skills in both groups Result: Based on the research result , the group of students who were given the addition of video learning media, has a higher average value (87.1) than the value average group of students who were not given video (80.3) and there is a significant difference in the value of the group of students receiving the video with the value of students who did not get video (p = 0.02) Conclusion: the provision of video learning media on CSL learning Blok 1.2 is quite effective in improving neuromotoric physical examination clinical skill of Medical students FKIK UNJA. Keywords: clinical skills, learning media, video, medical students